Aplicación de líneas de fertilizantes foliares en el cultivo de arroz (Oryza sativa), bajo Las condiciones Climáticas de Babahoyo, Provincia de Los Ríos - De Loor Almeida, Carlos Rafael (2019)
VIII. SUMMARY The present research work was carried out in the CEDEGE project, province of Los Ríos. Located at Km 12 of the Babahoyo - Montalvo highway; in the geographic coordinates 01 ° 53'23,3" S; 79 ° 24'45,6 "W and 9 masl. The annual average of precipitation is 2329.8 mm; 83 % relative humidity; 998.2 hours of heliophany and temperature of 25,0 ° C. The rice variety INIAP 11 was used as the sowing material. The treatments consisted of 4 foliar fertilizers; plus a control treatment without application. We used the experimental design Random Complete Blocks with five treatments and 4 repetitions, the test of significance used was Tukey at 95 % probability. All the necessary agricultural work was done in rice cultivation for its normal development as soil preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the following data were taken: plant height, number of tillers, number of panicles, length of panicles, grains per panicles, weight of 1000 grains, yield, partial productivity of nutrients, economic analysis. Based on the results obtained, it was determined that the fertilization programs used in treatments T1, T2, T3 and T4 did not show statistical differences in height with respect to T5 (control), being numerically the best treatment T1 (Complefol) with 125, 63 cm. Regarding the number of tillers / m2, there was no statistical significance, highlighting numerically the treatment T2 (Plantin) that presented better results with 484.0 tillers / m2. In the weight of 1000 grains did not present statistical significance, the treatment T2 (Plantin), was greater numerically to the rest of treatments with 36.5 g. The best yield obtained was from the T2 treatment (Plantin), where we reached 6285.5 kg / ha, unlike our lowest value with the T5 treatment (Control), with 5795.5 kg. Regarding the economic analysis, the cost fixed generated to produce a hectare of rice in this sector is $ 850, the greatest benefit was obtained by the treatment T2 (Plantin), with $ 441,96. Keywords: Foliar Fertilizers, Yields, Behavior.